1997
DOI: 10.1097/00000542-199709000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Produced by Inducible Nitric Oxide Synthase Delays Gastric Emptying in Lipopolysaccharide-treated Rats

Abstract: The present study suggests that NO, probably produced by iNOS, is one of the factors involved in the delay of gastric emptying in the LPS-treated rats and probably in those with sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
35
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 26 publications
7
35
0
1
Order By: Relevance
“…During late endotoxemia, iNOS inhibition also reversed, almost completely, the increase in gastric retention. This finding is consistent with a previous study in rats, in which iNOS inhibition with aminoguanidine (a selective iNOS inhibitor) administered 5 h after LPS administration partially reversed the delay in gastric emptying in late endotoxemia (2).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…During late endotoxemia, iNOS inhibition also reversed, almost completely, the increase in gastric retention. This finding is consistent with a previous study in rats, in which iNOS inhibition with aminoguanidine (a selective iNOS inhibitor) administered 5 h after LPS administration partially reversed the delay in gastric emptying in late endotoxemia (2).…”
Section: Discussionsupporting
confidence: 93%
“…Endotoxemia, which occurs after lipopolysaccharide (LPS) injection, delays gastric emptying and disrupts intestinal transit (1)(2)(3)(4)(5)(6)(7). However, it is not clear whether the latter effect involves a delay or acceleration since both have been reported (1,(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that exogenous NO has a prejunctional inhibitory effect on the nitrergic component of the NANC response, resulting from a down-regulation of nNOS (De Man et al, 1995). Studies of the effect of the endotoxin lipopolysaccharide on the GI tract have associated delay in gastric emptying and intestinal transit with increased expression of inducible NOS (iNOS) (Takakura et al, 1997;Fan et al, 2001;De Winter et al, 2002). The substantial concentrations of NO which can be generated by iNOS are known to autoinhibit the constitutive forms of NOS (cNOS), which may result in a condition in which iNOS is overexpressed, while cNOS is concurrently inhibited (Schwartz et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Doses of endotoxin that do not modify systemic arterial blood pressure or rectal temperature selectively decrease gastric acid secretion (Barrachina et al 1995a;Esplugues et al 1996;Martínez-Cuesta et al 1994), increase the mucosal resistance to damage (Barrachina et al 1995b) and decrease gastric emptying of non-nutrient, usually liquid, meals (Collares 1997;Cullen et al 1995;Takakura et al 1997;van Miert and de la Parra 1970). These effects of endotoxin do not appear to be the consequence of a local mechanism and seem to be mediated by reflex pathways involving extrinsic innervation of the gut.…”
Section: Introductionmentioning
confidence: 99%